Effects of Organic Nutrient Sources and NPS Fertilizer on the Agronomic and Economic Performance of Haricot Bean (Phaseolus vulgaris L.) in Southern Ethiopia. (17th August 2020) - Elka, Ermias; Laekemariam, Fanuel
Abstract : Despite the fact that mineral fertilizers are widely considered as a major option for addressing the crisis of nutrient depletion, their use among smallholder farmers is not adequate due to an escalating cost. Alternatively, nutrient-rich organic sources that are easily available to farmers are not widely promoted. Thus, this study was carried out in the research field of Wolaita Sodo University, Southern Ethiopia, to evaluate the effects of locally available organic nutrient sources and nitrogen (N) phosphorus (P) sulfur (S) fertilizer (19N-46P2 O5 -7S) on the productivity and economic performance of common bean. The organic materials used were Croton ( Croton macrostachyus ) and Erythrina ( Erythrina brucei ) at 2 : 1 ratio, respectively. The experiment was laid out in a randomized complete block design with three replications. Treatments for organic fertilizer (OF) were 0, 2.5, and 5 t·ha −1 and for NPS fertilizer were 0, 50, 100, and 150 kg·ha −1 . Chemical composition analysis of organic materials showed high nutrient content where the amount varied from 4.7%–5.2% N, 11.07–18.6 mg/kg P, and 2.12%–3.07% K. Results on agronomic parameters revealed that the leaf area index, grain weight, number of pods per plant, dry matter per plant, and grain yield of haricot bean were significantly affected by both main and combined effects of NPS and OF fertilizers. The grain yield under integrated application of 150 kg NPS/ha and 2.5 t·OF/ha (4.16 t/ha) was significantly higher than that obtained from unfertilized crop (1.01 t/ha) by 312%. Additionally, it resulted in 34%, 31%, and 79% yield increment over the blanket dose (100 kg·NPS·ha −1 ), 2.5 t/ha and 5 t/ha, respectively. It was also noted that resource-poor farmers, compared to unfertilized crop, can get grain yield superior by 130% and 214% using sole OF at 2.5 and 5 t·ha −1, respectively. Furthermore, the highest economic benefit (27, 179.5EtB) was recorded from 150 kg NPS/ha + 2.5 t·OF/ha. The finding suggested that locally available organic materials of plant origin alone/integrated with NPS fertilizer are helpful for increased yield of haricot bean.